ASSESING THE EFFECT OF ENVIRONMENTAL MANAGEMENT AND LEAN PRODUCTION SYSTEMS ON FIRM PERFORMANCE - Gök, Mehmet Şahin; Arici, Tugkan (Pressacademia, 2016)
Environmental management has increasingly become one of the key concerns of companies for effective utilization of their limited resources. Growing sensibility towards environmental issues mainly leads to increased costs for the companies and thus might reduce profitability. However lean production systems propose an alternative approach to improve both effectiveness and profitability by eliminating waste and non-value added transactions/activities. The main purpose of this study is to empirically analyze the relationship between environmental management and lean production systems as well as their effect on firm performance. The moderating effect of technological orientation between environmental management and firm performance is also examined. The model presented provides implications for both empirical research and company management in practice. Expected findings focus less on general statistical correlations and more on causal relationships of environmental management, lean production and firm performance. Consequently, implications and future research directions are also discussed according to the results.
Global Business Research Congress (GBRC) -- MAY 26-27, 2016 -- Istanbul, TURKEY
Keywords: Environmental management; lean production systems; firm performance; technological orientation